Surgical Fixation of Maisonneuve Fractures with a Screw Suture Fixation Device: Results of 10 Cases. Issue 4 (November 2022) - Swords, Michael P.; Schepers, Tim; Tomlinson, Matthew P.; Shank, John R.
Category: Trauma; Ankle; Sports Introduction/Purpose: Maisonneuve fractures consist of a fracture of the fibula in the proximal third with associated syndesmotic injury. Surgical management generally involves restoration of fibula length, reduction of the syndesmosis, and stabilization of the syndesmosis. Flexible fixation devices have gained popularity for syndesmotic fixation over the last several years. Current flexible fixation devices are not reliable for fixation of length unstable patterns of injury, like the Maisonneuve fracture. The purpose of the study was to evaluate the results of a new screw- suture syndesmotic device providing aperture fixation of the syndesmosis for fixation of Maisonneuve fractures. Methods: 10 consecutive patients with Maisonneuve injuries were treated with indirect restoration of fibula length, open reduction of the syndesmosis, and stabilization of the syndesmosis with the screw suture device. Talocrural angle and medial clear space was measured and recorded at time of injury, post operatively and 6 months. Rate of hardware removal was recorded.***2 patients are 2 months short of 6 months. both have healed their proximal fibula fractures so no changes to data are anticipated *** Results: There were 5 males and 5 females. 5 patients slipped on ice, 4 patients fell on uneven walking surfaces, 1 patient was in a motorcycle accident. 2 patients had associated posterior malleolus fractures, 1 was fixed with a posterior plate. 1 patient had a medial malleolus fracture repaired with 2 screws. 9 devices were placed independently. 1 device was inserted through a 4 hole 1/3 tubular plate. Average time to surgery was 12.3 days (range 5-24 days). Talocrural angles averaged 8.92 (4.8-14.5mm) on injury films, 13.8mm (10.6-17mm) post operatively and 13.5mm (10.6-16.6) at 6 months. Medial clear space measurement averaged 5.68mm (2-10mm) on injury films, 2.06mm (1.9-2.3mm) post operatively and 2.1mm (2-2.3mm) at 6 months. No devices required removal during the study period. Conclusion: The screw-suture device provided length stable fixation for treatment of Maisonneuve fracture patterns.